Цари и самозванцы: (рассказы о Смутном времени) / С. Алексеев, В. Алексеева - Алексеев Сергей Петрович (Логосвос, 2017)
Экземпляры: БС (20171221) / Инвентарный номер: РТШ54653 / Цена: / Сис.шифр: 63.3(2)4 / Авт.знак: А 47 / ГРНТИ: 03.23.25 / ББК: 63.3(2)44